Philosophy and rhetoric: Plato's critique of the sophists - Numpaque García, Julián Ramiro (2023)
This article aims to point out that Plato’s criticism of Sophists and rhetoric is not a condemnation of them, but a distance from traditional rhetoric in order to introduce his proposal for a philosophical rhetoric. For this objective, the aim is to: 1) outline the definition of the concepts ‘rhetoric’ and ‘sophistic’, and characterize the principles of ‘sophistic rhetoric’; 2) To address Plato’s criticism of the sophists from the Gorgias, pointing out the arguments with which Plato criticizes the rhetoric and the Sophists; 3) To analyze the dialogical method of the Sophists (eristics) and how it opposes the philosopher’s method (dialectic); 4) Finally, to point out, starting from the Phaedrus, Plato's foundations for the consolidation of a ‘philosophical rhetoric’, that is, of a genuine philosophical dialogue that serves as an overcoming of traditional rhetoric.